ANALISIS STUDI KELAYAKAN BISNIS PADA KELOMPOK USAHA AFINITAS TUNAS HARAPAN BARU KOTA BATU - Muhamad Rifa’i; Totok Sasongko; Poppy Indrihastuti; Feronnika Feronnika (OPTIMA, 2018)
The purpose of this research was to analyze the feasibility of oyster mushroom cultivation venture white small and medium enterprises Cultivation Oyster mushrooms on the Group Affinity “Tunas Harapan Baru” in terms of financial aspect. Research conducted is a research application model, data that is used for data that is processed by the rekapan financial statements and investment amount of data that is used in an attempt to match a description patrons Group Affinity “Tunas Harapan Baru”. Data collection techniques are used i.e., interview, observation, and documentation. Data analysis methods in use is composed of Financial aspects of the Analysis method of payback period, net present value, internal rate of return, and profitability index. Results of the study shows the effort which implemented the terms of the financial aspect was feasible. It is based on the results of the analysis of the payback period of 8.8 (8 months 8 days), the value of the net present value of 16,659 million, the value of the internal rate of return of 3.70 and profitability index of 2.70 where oyster mushroom business revealed profitable and feasible in terms of financial or in terms of management. The bussines development could be held by making the great outline of bussines based on the result of group evaluation over all so that it will get the profitable bussines. Key words: feasibility study, financial aspects.